0
$\begingroup$

Can someone elaborate on what rules underlie the rule

$-a+b=b-a\;?$

Is it associative properties of multiplication and addition? For example,

$-a+b=b-a$

$(-1)(a)+b=b-a$

$b+(-1)(a)=b-a$

$b-a=b-a$

Are there any exceptions to $-a+b=b-a$?

$\endgroup$
1
  • 4
    $\begingroup$ I would say commutativity of addition and definition of subtraction as addition of the additive inverse $\endgroup$ Feb 12 '19 at 3:41
2
$\begingroup$

We don't have to invoke any properties of multiplication to explain why $-a+b=b-a.$ We don't have to invoke associativity (which refers to different ways of grouping three operands) either. We merely have to know that addition is commutative (i.e., $x+y=y+x$) and every element $z$ has an additive inverse ($-z$) such that $z+ (-z) = 0.\;$ We define subtraction by $x-z=x + (-z)$. In any system where those assumptions hold, it is always true that $(-a) + b = b + (-a) = b -a$.

$\endgroup$
2
$\begingroup$

The commutative property of addition.

$$x+y = y+x$$.

Set $x = -a$ and $y=b$.

There are no exceptions.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.